Organizational Commitment of a Non-Teaching Personnel in a State University in the Philippines - Elisa P. Payod, Marvin S. Canque, Lloyd Matthew C. Derasin (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to assess the relationship between the length of service and employment status and the level of affective, continuance, and normative organizational commitment of the non-teaching personnel in the state university. It is also aimed to assess the difference in organizational commitment between the rank-and-file employees and the head of office. This study used a descriptive correlational method design. A total of thirty-four (34) head of office and eighty-two (82) rank and file employees are the actual respondents of the study. The data were collected using a structured questionnaire adapted from Meyer and Allen’s organizational commitment and analyzed using a t-test of independent samples and Pearson’s r correlation. The findings revealed that employment status and service length are positively associated with the affective and normative level of organizational commitment. Moreover, the findings revealed a significant difference in the level of normative organizational commitment between the head of office and rank and file employees. It is concluded that an employee’s affective and normative commitment is affected by the length of service and individual’s security of tenure and position level in the institution. It is recommended that the administration should recognize the contribution of the non-teaching personnel, particularly the rank-and-file in the institution. Thus, the top management must include in their priority plans and programs the upgrading of the employment position/status of the employee to sustain the level of organizational commitment as it is intricately linked to work performance.